Legal-criminological analysis of the impact of the Covid-19 pandemic on domestic violence A case study of Mashhad women - Hamidreza Danesh Nari; akram khabiri noghani (فقه و حقوق خانواده)
The emergence of Covid-19 since 2019 has brought the world with various challenges. The important effect of Covid-19 in the field of criminology studies is the change in the algorithm of patterns of delinquency, victimization and fluctuation in the rates of various crimes. According to the health guidelines and the formation of campaigns such as "stay at home", explaining the crime of domestic violence is of great importance during the pandemic period. Based on this, the current research seeks to investigate the role of Covid-19 on domestic violence. The present research method is a combination of qualitative and quantitative methods. At first, using the descriptive phenomenological method of Clause, the lived experience of ten women victims of domestic violence during the pandemic period was obtained. Following the stages of the Clause method, the researcher-made questionnaire was designed in the light of lived experiences and with an emphasis on physical violence, mental violence, verbal violence, sexual violence and economic violence, and its validity, form and structure and reliability were confirmed. The statistical population of this research in the quantitative study section is all female teachers of the second secondary level in the 7th education district of Mashhad, from which, using the simple random sampling method and in the light of Cochran's formula, 190 people were selected as the final sample size. . The results of the one-variable test showed that physical violence, mental violence, verbal violence, sexual violence and economic violence have increased as a direct result of the spread of Covid-19 compared to the pre-pandemic period. However, the findings of Friedman's test proved that among the types of violence, physical violence ranks first and psychological violence ranks last.